Dexmedetomidine Attenuates Inflammation in Elderly Patients Following Major Hepatobiliary and Pancreatic Surgery: A Randomized Clinical Trial [Corrigendum] - Chen X; Chen Q; Qin Z; Alam A; Zhao H; West R; Liu X; Li J; Li X; Yi B; Ma D; Gu J (Clinical Interventions in Aging)
Chen X, Chen Q, Qin Z, et al. Clin Interv Aging. 2024;19:981—991. The authors have advised due to an error at the time of figure assembly, Figure 3B on page 987 is incorrect and is a duplication of Figure 3A. The correct Figure 3 is shown below.